Populasi dan Spesies Serangga Hama di Gudang dari Empat Pasar Lokal dengan Struktur Bangunan, Pencahayaan, Lantai yang Berbeda di Kecamatan Ilir Barat I, Ilir Barat II, Gandus, Palembang Sumatera Selatan - Abbellia, Dea; Herlinda, Siti; Setyawati, Anita; Yulistin, Eka; Anggraini, Erise; Merlisma Sari, Selvy; Triyanti, Yunita; Prayudi, Rafi; Barokah Alburaidah, Muhammad Nur; Trianza Putri, Anya (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Abbellia, D., Herlinda, S., Setyawati, A., Anggraini, E., Sari, M. S., Triyanti, Y., Prayudi, R., Alburaidah, B. M. N., & Putri, T. A. (2024). Population and storage pest species from four local markets with various building structures, lighting, and floors in Sub-District Ilir Barat I, Ilir Barat II, Gandus, Palembang,South Sumatera. In: Herlinda S et al. (2024.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 221–234). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Sitophilus oryzae is a pest insect that can cause up to 31% product damage because pests can spread rapidly from harvest to storage. The aimed of this study was to identify the various storage pest species present in four local markets. The researcher determined the objectives and conducted field observations using survey methods and purposive sampling techniques. The results of the data collection were presented in the form of descriptive images and anova. This study identified the warehouse at Four Market based on the results. Several pest species were found, namely Tribolium castaneum, Sitophilus oryzae, Callosobruchus chinensis, Rhyzopertha dominica, Oryzaephillus surinamensis, Cryptolestes ferrugineus, and Carpophillus dimidiatus by means of visual physical examination of random methods on several commodities. The results of the analysis showed that in the market of Ilir Barat I sub-district, 7 species of warehouse pests were found. We found 4 species of warehouse pests in the Ilir Barat II Subdistrict Market, and another 4 species in the Gandus Subdistrict Market. Commodities attacked by warehouse pests include rice, green beans, peanuts, and flour. The outcomes of lighting assessments at the four market locations were favorable for Ilir Barat I subdistrict Market and Gandus subdistrict. Nevertheless, the Ilir Barat II sub-district exhibited marginally inferior illumination. The species in the Ilir Barat II subdistrict exhibited greater infection levels due to inadequate illumination, in contrast to the Ilir Barat I Market, which benefited from superior lighting, resulting in a lower infestation percentage.